Developing Leadership Skills Through Simulation-Based Training: A Research Framework and Interpretive Case Study - Barbaroux, Pierre (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
Despite a growing consensus regarding the significance of critical inquiry, reflective thinking and experimentation in driving much of leadership training, we still lack empirical evidence on how pragmatist approaches to learning (e.g. game-based learning, simulation-based training) actually support the development of leadership skills. In particular, little is known about the interplay between multiple factors (i.e., instructional features, trainees’ profile, socio-cultural norms) enabling simulation-based training, and how it affects the consolidation of heterogeneous types of leadership skills. To fill these gaps, this article establishes a conceptual framework based on three propositions, and assesses its validity through an interpretive case study.